2021
DOI: 10.3390/ijerph18030892
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Approaches to Reducing Health Inequities and Fostering Environmental Justice through Global Youth-Engaged Citizen Science

Abstract: Growing socioeconomic and structural disparities within and between nations have created unprecedented health inequities that have been felt most keenly among the world’s youth. While policy approaches can help to mitigate such inequities, they are often challenging to enact in under-resourced and marginalized communities. Community-engaged participatory action research provides an alternative or complementary means for addressing the physical and social environmental contexts that can impact health inequities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 66 publications
3
85
0
6
Order By: Relevance
“…For example, Vargas et al 21 suggested that the active participation of parents in school‐based intervention activities may simultaneous promote social cohesion, further reinforcing the effectiveness of these types of multicomponent interventions particularly with underserved populations. The positive effects of active parent and student participation also were observed in the Latinx/Latin American citizen science studies 109 . A potential benefit achieved by researchers and practitioners who have considered how best to reach and serve groups who are more collectivistic and family‐oriented is that they have been less likely to consider the problem of overweight and obesity in isolation from the social context, a problem that has occurred in other obesity‐related research 120 …”
Section: Discussionmentioning
confidence: 88%
“…For example, Vargas et al 21 suggested that the active participation of parents in school‐based intervention activities may simultaneous promote social cohesion, further reinforcing the effectiveness of these types of multicomponent interventions particularly with underserved populations. The positive effects of active parent and student participation also were observed in the Latinx/Latin American citizen science studies 109 . A potential benefit achieved by researchers and practitioners who have considered how best to reach and serve groups who are more collectivistic and family‐oriented is that they have been less likely to consider the problem of overweight and obesity in isolation from the social context, a problem that has occurred in other obesity‐related research 120 …”
Section: Discussionmentioning
confidence: 88%
“…Youth then meet in a facilitated process, either in‐person or through a remote, web‐based meeting platform, to share their data and build consensus around high priority issues and potential solutions. The Our Voice process has also been found to strengthen individuals' personal and collective efficacy for changing behaviors and their local environments and policies 70,75,76 …”
Section: Resultsmentioning
confidence: 99%
“…The Our Voice process has also been found to strengthen individuals' personal and collective efficacy for changing behaviors and their local environments and policies. 70 , 75 , 76 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is helpful to engage with people and organizations that play a gatekeeping or “bridging” role between health care or scientific team members and the community, 24 such as community organizers or liaisons who understand the Latin x community being served and are viewed as credible and trusted 26 . In addition, employing systematic methods for including the voices of community residents themselves, critical to enrich the information being gathered and acted upon, is been increasingly recognized 27,28 . The scientific members of the team should also be multidisciplinary, ideally integrating expertise in health and medicine, child development, social and cultural sciences, health policy, community psychology, data/analytic sciences, and systems science.…”
Section: An Action‐oriented Framework For Systems Changes For Childhood Obesity Preventionmentioning
confidence: 99%